2021
DOI: 10.1097/ta.0000000000003104
|View full text |Cite
|
Sign up to set email alerts
|

Trauma patients at risk for venous thromboembolism who undergo routine duplex ultrasound screening experience fewer pulmonary emboli: A prospective randomized trial

Abstract: Trauma patients are at high risk for venous thromboembolism (VTE) if they do not receive adequate chemoprophylaxis. The occurrence of deep vein thrombosis (DVT) and pulmonary embolism (PE) following trauma is well established. ScopeAll patients admitted to the Intermountain Medical Center Trauma Service. DefinitionsBID -Twice a day BMI -Body mass index DOAC -Direct oral anticoagulant DUS -Duplex ultrasound IVC -Inferior vena cava LOC -Loss of consciousness PO -By mouth (orally) SCDs -Sequential compression dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…APE is a common clinical emergency with a complex etiology. Previous studies believed that the occurrence of APE was related to factors such as long-term bed rest and chronic lung disease [ 14 ]. APE was easy to cause AF, which posed a threat to patients' life safety, so the hidden danger of APE complicated with AF cannot be ignored [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…APE is a common clinical emergency with a complex etiology. Previous studies believed that the occurrence of APE was related to factors such as long-term bed rest and chronic lung disease [ 14 ]. APE was easy to cause AF, which posed a threat to patients' life safety, so the hidden danger of APE complicated with AF cannot be ignored [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…thromboembolism reported a significant reduction in pulmonary embolism incidence using screening duplex ultrasound of the lower extremities. 29 The disadvantage is that anticoagulation may be initiated for a thrombus that may not become symptomatic, which increases the risk of bleeding in a patient that did not need to be anticoagulated. 30 Recent guidelines from the American Association of Surgery for Trauma (AAST) recommend screening for thromboembolism in high-risk patients, although high risk is not defined.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical value of active screening is that it allows for earlier detection of thrombosis and the initiation of anticoagulation if appropriate 28 . For example, an RCT of approximately 2000 trauma patients at moderate to high risk of thromboembolism reported a significant reduction in pulmonary embolism incidence using screening duplex ultrasound of the lower extremities 29 . The disadvantage is that anticoagulation may be initiated for a thrombus that may not become symptomatic, which increases the risk of bleeding in a patient that did not need to be anticoagulated 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, routine duplex screening in patients with high-risk injury patterns may be justified 37 and cost-effective 38 . A prospective randomized trial published in 2021 found that screening in patients with high risk-assessment scores was associated with fewer PE 39 . The added benefit of this approach over and above a rigorous protocol for timely pharmacologic prophylaxis remains uncertain.…”
Section: A Brief History Of Vte Research In Injured Patientsmentioning
confidence: 99%